Factors Affecting Organizational Commitment of Employees at Lao Friends Hospital for Children in Luang Prabang Province - Chittaphon, Southida (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aimed to 1) examine the level of organizational commitment, 2) assess employee perceptions of work environment factors, and 3) factors affecting organizational commitment of employees at Friends Hospital for Children. The sample comprised 138 employees. Data were gathered using a highly reliable structured questionnaire. Statistical analyses included frequency, percentage, mean, standard deviation (S.D.), and Multiple Regression Analysis. The findings revealed that 1) The overall organizational commitment was at the "Highest" level ( = 4.46, S.D = 0.57), with continuance commitment scoring the highest mean ( = 4.64), 2) Employee perceptions of the work environment were also at the “Highest” level ( = 4.21); at the dimension level, system maintenance and change dimension rated the highest ( = 4.17, S.D = 0.58), while task orientation (X5) ( = 4.27) and peer cohesion (X2) ( = 4.26) led at sub-factor level, 3) Multiple regression analysis indicated that work environment factors significantly explained 64.9% of the variance in overall organizational commitment (R2 = 0.649). Five independent variables were found to have statistically significant effects at the 0.10 level. These include task orientation (X5) (β = 0.482), peer cohesion (X2) (β = 0.301), autonomy (X4) (β = 0.288), supervisor support (X3) (β = 0.215), and innovation (X9) (β = 0.148). Among these, task orientation demonstrated the strongest predictive power, indicating that employees who are more focused on work performance and goal achievement tend to exhibit higher levels of organizational commitment. This research aimed to 1) examine the level of organizational commitment, 2) assess employee perceptions of work environment factors, and 3) factors affecting organizational commitment of employees at Friends Hospital for Children. The sample comprised 138 employees. Data were gathered using a highly reliable structured questionnaire. Statistical analyses included frequency, percentage, mean, standard deviation (S.D.), and Multiple Regression Analysis. The findings revealed that 1) The overall organizational commitment was at the "Highest" level ( = 4.46, S.D = 0.57), with continuance commitment scoring the highest mean ( = 4.64), 2) Employee perceptions of the work environment were also at the “Highest” level ( = 4.21); at the dimension level, system maintenance and change dimension rated the highest ( = 4.17, S.D = 0.58), while task orientation (X5) ( = 4.27) and peer cohesion (X2) ( = 4.26) led at sub-factor level, 3) Multiple regression analysis indicated that work environment factors significantly explained 64.9% of the variance in overall organizational commitment (R2 = 0.649). Five independent variables were found to have statistically significant effects at the 0.10 level. These include task orientation (X5) (β = 0.482), peer cohesion (X2) (β = 0.301), autonomy (X4) (β = 0.288), supervisor support (X3) (β = 0.215), and innovation (X9) (β = 0.148). Among these, task orientation demonstrated the strongest predictive power, indicating that employees who are more focused on work performance and goal achievement tend to exhibit higher levels of organizational commitment.